Dynamic modeling and control of nonholonomic mobile robot with lateral slip - Sidek, Shahrul Na'im; Sarkar, Nilanjan (2008)
Nonholonomic mobile robots are characterized by no-slip constraints. However, in many practical situations, slips are inevitable. In this work, we develop a theoretical and systematic framework to include slip dynamics into the overall dynamics of the wheeled mobile robot (WMR). Such a dynamic model is useful to understand the slip characteristics during navigation of the WMR. We further design a planner and a controller that allow efficient navigation of the WMR by controlling the slip. Preliminary simulation results are presented to demonstrate the usefulness of the proposed modeling and control techniques.